Faktor Yang Berhubungan dengan Perilaku Ibu Rumah Tangga dalam Mengelola Sampah di Desa Satar Nawang Kecamatan Congkar Kabupaten Manggarai Timur - Theresia Cintia Norasari; Afrona E. L. Takaeb; Dian Lestari Anakaka (Yayasan Literasi Sains Indonesia, 2023)
The household waste management is still one of the public health problems in Satar Nawang Village. This study aims to determine the factors related to housewives' behavior in managing waste in Satar Nawang village, Congkar district, east Manggarai regency. The research method used is observational analytical research with a cross-sectional study design. The population in this study were all housewifes in Satar Nawang Village, totaling 276 people, and the sample consisted of 161 people taken using simple random sampling technique. The researchers collected data through observation, interviews, and questionnaires as instruments in data collection. The data was then analyzed using the Spearman correlation test (ρ) with a significance level of (α = 0.05). The results of this study showed that there were three variables that had a correlation with the behavior of housewifes in managing waste, namely education level (p = 0.001), income (p = 0.018), and knowledge level (p = 0.013), while employment status had no correlation with the behavior of housewifes in managing waste (p = 0.087). Education has a low correlation with waste management behavior, while income, employment status, and knowledge level have a very weak correlation with waste management behavior. It is expected that the government will provide waste disposal facilities such as temporary holding area and health workers to conduct education and outreach on waste sorting, and for housewifes themselves to properly dispose of waste such as sorting waste before disposing of it, not burning dry waste and not leaving waste scattered around the house.